What do we actually know about math learning strategies? - Stefan Büchele (Philipps-University Marburg, School of Business and Economics, 2022)
Various studies investigate the effects of learning strategies on students' (math) performance. However, particularly in math, one can see a mixed pattern of the impact of learning strategies on performance. This is probably because of different methodological approaches, leading to different results. This study investigates the effect of learning strategies on math performance within different statistical and methodological approaches using a sample of 299 undergraduate students enrolled in Economics and Business Administration at a midsized German university and compares the different outcomes. On the one hand, the results suggest that most studies probably report biased estimations, which are not trustworthy. On the other hand, those learning strategies might not be as important as educational researchers and practitioners think.
Keywords: 330; math performance; learning strategies; omitted variables; higher education